Correlation between hepatitis B surface antibody (anti-HBs) in maternal blood and cord blood in newborn: a study on transplacental acquired maternal antibody - Yudith Setiati Ermaya; Eka Surya Nugraha; Dolvy Girawan; Nelly Amalia Risan; Muhammad Begawan Bestari; Raden Tina Dewi Judistiani; Tetty Yuniati; Dwi Prasetyo (BMC Pediatrics)
Abstract Background Hepatitis B Virus infection is a global health problem. Transplacental maternal antibodies can protect the infant early in life from infection. Objectives: This study investigates the correlation between maternal and infant Hepatitis B surface antibodies (anti-HBs) in pairs. Methods This cross-sectional study measured anti-HBs in paired mother-infant samples. Blood samples were taken from the mother 3 h before delivery and from the newborn immediately after birth by cord blood, and they were then examined for anti-HBs using the Chemiluminescent Microparticle Immunoassay. Results Transplacental transfer of maternal anti-HBs was analyzed in 79 mother-infant pairs. Seventeen mothers (21.5%) had positive anti-HBs and all cord blood of newborns from these mothers had anti-HBs detected. Overall, there were 44 (55.7%) newborn blood cords that were positive for anti-HBs. The geometric mean of anti-HBs cord blood titers in newborns with maternal anti-HBs titers < 10, ≥10, ≥ 100, and ≥ 1,000 mIU/mL were 52.42, 193.83, 437.12, and ≥ 1,000 mIU /mL respectively. This study showed a significant correlation in anti-HBs between mother and infant cord blood (r = 0.863; p < 0,001). Conclusions Anti-HB antibodies measured in mother and infant cord blood were strongly correlated, demonstrating efficient transplacental antibody transfer to protect infants against Hepatitis B infection. Hepatitis B vaccination is required for mothers to obtain immunogenicity and babies to receive hepatitis B vaccination on time.